Revisiting the debate on the Africanisation of higher education: an appeal for a conceptual shift - Letsekha, Tebello (My University, 2013)
Forming part of post-colonial discourse, Africanisation is often described as a renewed focus on Africa and entails salvaging what has been stripped from the continent. Applied to higher education it can be viewed as a call to adapt curricula and syllabuses to ensure that teaching and learning are adapted to African realities and conditions. Given the decontextualised state of curricula and dependent nature of knowledge production and dissemination in South African higher education, the concept of ‘Africanisation’ may be worth revisiting. This article reviews the literature in the debate on the Africanisation of higher education highlighting the strengths and weaknesses in the discourse; the paper also makes a case for endogenisation as an alternative to indigenisation
Keywords: Africanisation, indigenisation, internationalisation.